Fault Coverage and Diagnosis of Protocols and Systems Modeled As Extended Finite State Machines - Hassoun, Mark Habib (2015)
A Master of Science thesis in Computer Engineering by Mark Habib Hassoun entitled, "Fault Coverage and Diagnosis of Protocols and Systems Modeled As Extended Finite State Machines," submitted in January 2015. Thesis advisor is Dr. Khaled El-Fakih Available in both soft and hard copy.